Carbon coating and Al-doping to improve the electrochemistry of Li2CoSiO4 polymorphs as cathode materials for lithium-ion batteries. Issue 40 (21st June 2018) - Du, Hongwei; Zhang, Xianhui; Chen, Zhenlian; Wu, Dongyang; Zhang, Zhifeng; Li, Jun
Abstract : Conductive carbon framework, stable polymorphs, and the control of impurity are crucial to achieve advanced performance for insulating Li2 CoSiO4 . Abstract : Li2 CoSiO4 has the potential for use as a high safety, high energy-density cathode material for lithium-ion batteries but suffers from bad electrochemical performance. Herein, we demonstrate a profound study on the effects of carbon coating and Al-doping on the electrochemistry of Li2 CoSiO4 synthesized by a two-step method. The synthesized 4 at% Al-doped Li2 CoSiO4 /C allows two lithium removals between 2.5 and 4.6 V, showing a first charge and discharge capacity of 331 and 140 mA h g −1, respectively, and a high capacity retention in cycling with no voltage degradation. The relationship between the improved performance and the supporting structural characteristics was studied by galvanostatic charge/discharge measurements and electrochemical impedance spectroscopy, coupled with material characterizations. This work demonstrates that electrical conductivity plays a central role in controlling the electrochemical performance of the modified Li2 CoSiO4 . Both the reversibility of delithiation and the irreversible capacity loss are strongly dependent on the electrical condition of the particles, which can be modified by Al-doping and carbon coating. The characteristics of carbon layers are analyzed because of their importance in improving the electrical properties and achieving a solution to the challenges with Li2 CoSiO4 . We that show Li2 CoSiO4 could have unique electrochemical characteristics that satisfy all the requirements of high safety, high energy density, and high compatibility with the current organic electrolytes if appropriately modified.